Using the Bible in post-apartheid South Africa: Its influence and impact amidst the gay debate - Punt, J. (HTS teologiese studies, 2006)
The Bible has generated a significant reception history in the first decade of democratic, post-apartheid South Africa. Its reception history testifies to how the Bible was considered to be important across a broad spectrum of society, also contributing to believers’ lives and sense of self amidst the enormous changes in the country. Recent documents and decisions of the Dutch Reformed Church on homosexuality and the ensuing debates, highlight the influence and impact of Bible use in South Africa today. Examining different hermeneutical approaches to the Bible and using insights from reception theory, a number of interesting trends in the ongoing use and influence of the Bible are highlighted and discussed.